Investigation of the epitope specificities of antibodies to islet β-cell autoantigens - Al-bukhari, Talat Abdullah (2001)
Glutamic acid decarboxylase-65 (GAD-65) and the tyrosine phosphatase-like protein IA-2 are major targets of autoimmunity in type I diabetes mellitus (type I DM), stiff-man syndrome (SMS) and autoimmune polyendocrine syndrome (APS). In this study, the precise epitopes in GAD-65 of three different mouse monoclonal antibodies (MoAbs) (N-terminal MoAb within amino acid residues 4-17. C-terminal MoAb within amino acid residues 572-585 and GAD-6). human monoclonal antibody (b96.11 huAb) and polyclonal antibodies (SMS patients' sera) were investigated. The precise epitopes in IA-2 of two different MoAbs (76B and 76F) were also investigated. These precise epitope investigations were performed using two different phage-displayed random peptide libraries with different characteristics (T7 phage library gene X C9C and linear 9-mers, and M13 filamentous phage library gene III C7C and linear 12-mers and gene VIII 5C4C4).